Bottle Beams in Nonlocally Defocusing Nonlinear Media - Yuanqiang Peng; Yunqi Li; Xiaolin Wu; Weiyi Hong (IEEE Photonics Journal)
The dynamics of the inward-focusing ring Airy beam in nonlocally defocusing nonlinear media is investigated in detail, and a bottle beam shape can be observed by adjusting the amplitude of the inward-focusing ring Airy beam and the nonlocality of the media. The gradient force of the bottle beam is numerically studied. It is worth mentioning that the bottle beams are formed in the nonlinear regime, which indicates that much higher intensity is allowable for these beams than those in the linear regime. Our approach and results may pave the way to the optical tweezers in the nonlinear regime.